2012
DOI: 10.1074/jbc.m111.310409
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of Glu521 or Glu535 in Cytoplasmic Loop 5 Causes Differential Misfolding in Multiple Domains of Multidrug and Organic Anion Transporter MRP1 (ABCC1)

Abstract: Background:The five-domain MRP1 mediates ATP-dependent efflux of drugs and organic anions. Results: Chemically rescued cytoplasmic loop 5 (CL5) processing mutants of MRP1 exhibit distinct phenotypes characterized by differences in transport activity and protein conformation. Conclusion: Glu 521 and Glu 535 are important for folding of their resident domain as well as more COOH-proximal domains. Significance: MRP1 folding processes differ from those of its homologs including CFTR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…In vitro experiments suggest that breast cancer related protein (BCRP) [101], CFTR (ABCC7) [102,103], MRP1 (ABCC1) [104], ABCB1 and SUR1 (ABCC8) can be rescued by small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro experiments suggest that breast cancer related protein (BCRP) [101], CFTR (ABCC7) [102,103], MRP1 (ABCC1) [104], ABCB1 and SUR1 (ABCC8) can be rescued by small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Still others lead to misfolding and lower levels of MRP1 at the plasma membrane Iram and Cole, 2012). Consequently, we wondered if the discordance between the effects of the ABCC1 nsSNPs predicted in silico and our experimental data were due to limitations of the SIFT and PolyPhen algorithms and/or because the functional assays used were not sufficiently comprehensive to detect all possible phenotypic changes.…”
Section: Introductionmentioning
confidence: 99%
“…Because the functional changes detected for A989T and C1047S were the most significant among all the nsSNPs tested, we determined whether any of these changes were associated with any differences in protein conformation as reflected by a change in protease susceptibility. Thus, membrane vesicles enriched for wild-type and mutant MRP1 were digested with a range of trypsin/ protein ratios, and tryptic fragments were detected by immunoblotting with a panel of antibodies that detect epitopes in different domains of the transporter (Iram and Cole, 2012). Tryptic digests were performed in the presence and absence of S-methyl GSH because previous studies have shown that this tripeptide (and the less stable GSH) can stimulate substrate transport (and modulate inhibitor activity) as well as alter the conformation of MRP1 (Loe et al, 1998;Mao et al, 2002;Peklak-Scott et al, 2005;Ren et al, 2005;Rothnie et al, 2006;Cole, 2013).…”
Section: Bioinformatic Analyses Of Predicted Consequences Of Mrp1mentioning
confidence: 99%
See 2 more Smart Citations